School Principal Leadership in Improving Teacher Performance in Kindergarten Tut Wuri Handayani - Fajri, Yulia; Syarfuni, Syarfuni; Zahraini, Zahraini (Jurnal Ar Ro'is Mandalika (Armada), 2021)
The purpose of this study was to determine the leadership applied by the principal to improve the performance of Tut Wuri Handayani Kindergarten teachers to work more effectively and efficiently. The method used in the research is a descriptive approach with qualitative analysis, namely by using data collection techniques in the field through the process of interviews, observation and documentation. The results showed enhance teacher performance, the principal leads the team in finishing assignments and work within the allotted time. The orientations peer interactions and task orientation show how teacher performance has improved at Tut Wuri Handayani Kindergarten. The principal effectively carries out the laws aimed at enhancing teacher performance, carries out programs that develop teaching ability by encouraging teachers to pursue further education, and recognizes and rewards the hard work and dedication of their teachers.